Contribution of Fibrosis and the Autonomic Nervous System to Atrial Fibrillation Electrograms in Heart Failure - Koduri, Hemantha (2012)
BACKGROUND: Fibrotic and autonomic remodeling in heart failure (HF) increase vulnerability to atrial fibrillation (AF). Since AF electrograms (EGMs) are thought to reflect underlying structural substrate, we sought to: a) determine differences in AF-EGMs in normal versus HF atria and b) assess how fibrosis and nerve-rich fat contribute to AF-EGM characteristics in HF. METHODS AND RESULTS: AF was induced in 20 normal dogs by vagal stimulation and in 21 HF dogs (subjected to 3 weeks of rapid ventricular pacing at 240/min). AF-EGMs were analyzed for dominant frequency (DF), organizational index (OI), fractionation intervals (FI) and Shannon's entropy (ShEn). In 8 HF dogs, AF-EGM correlation with underlying fibrosis/fat/nerves was assessed. In HF, compared to normals, a) DF was lower and OI/FI/ShEn were greater. DF/FI were more heterogeneous in HF. %fat was greater, and fibrosis and fat more heterogeneously distributed in the posterior left atrium (PLA) than left atrial appendage (LAA). DF/OI correlated closely with %fibrosis. Heterogeneity of DF/FI correlated with heterogeneity of fibrosis. Autonomic blockade caused a greater change in DF/FI/ShEn in the PLA than LAA, with the decrease in ShEn correlating with %fat. CONCLUSIONS: The amount and distribution of fibrosis in the HF atrium appears to contribute to slowing and increased organization of AF-EGMs, while the nerve-rich fat in the HF-PLA is positively correlated with AF-EGM entropy. By allowing for improved detection of regions of dense fibrosis and high autonomic nerve density in the HF atrium, these findings may help enhance the precision and success of substrate-guided ablation for AF.